Georgia : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2003)
The Economic Development and Poverty Reduction Program (EDPRP) was developed with the active participation and support of society, executive authorities, nongovernment organizations, academia, businessmen, and donors. The study additionally provides coordinated mechanisms for bilateral and multilateral international economic relations. In preparing this strategy, the government was ably assisted by the international donor community, including the IMF and World Bank, the European Union, and the governments of the United States, Great Britain, the Netherlands, and Germany, as well as other organizations and governments.